2015
DOI: 10.2319/111013-823.1
|View full text |Cite
|
Sign up to set email alerts
|

Hounsfield Units: A new indicator showing maxillary resistance in rapid maxillary expansion cases?

Abstract: Objective: To determine if density measurements of several maxillary regions in Hounsfield Units (HU) and outcomes of rapid maxillary expansion (RME) are correlated. Is correlation powerful enough to give us direct information about maxillary resistance to RME? Materials and Methods: Twenty-two computed tomographic (CT) scans (14 years) are used in this archive study. Two CT records were collected, one before RME (T 1 ) and one after 3 months of retention period (T 2 ). Maxillary measurements were made using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…This finding is consistent with previous observations in which a low-dose CT image was used [17,18], thus indicating further that a retention period longer than 3 months may be appropriate for recovering the bone mineral density of the midpalatal suture, reducing the amount of skeletal relapse [3,6,15]. Skeletal relapse may be a result of a reactive force, called the buttressing effect, which develops against the expansion forces according to patient age, and the circummaxillary bone rigidity [34]. The present study revealed a higher increase in BD at the anterior (AP ROI) and posterior regions (PP ROI) compared with the middle portion of the suture (AMP and PMP ROIs) during the retention period, not confirming the posteroanterior closing pattern (like a "zip") of the midpalatal suture [25].…”
Section: Discussionsupporting
confidence: 89%
“…This finding is consistent with previous observations in which a low-dose CT image was used [17,18], thus indicating further that a retention period longer than 3 months may be appropriate for recovering the bone mineral density of the midpalatal suture, reducing the amount of skeletal relapse [3,6,15]. Skeletal relapse may be a result of a reactive force, called the buttressing effect, which develops against the expansion forces according to patient age, and the circummaxillary bone rigidity [34]. The present study revealed a higher increase in BD at the anterior (AP ROI) and posterior regions (PP ROI) compared with the middle portion of the suture (AMP and PMP ROIs) during the retention period, not confirming the posteroanterior closing pattern (like a "zip") of the midpalatal suture [25].…”
Section: Discussionsupporting
confidence: 89%
“…The effect of treatment has been shown to be midpalatal suture separation with the defect then created reported to be rapidly filled with new bone [10]. Dimensional changes in the midpalatal suture produced by RME in growing subjects have been investigated by conventional radiographic techniques [11] and cone beam computed tomography (CBCT) [12,13]. Radiographic studies showed significant density reduction along the midpalatal suture at the end of active expansion and an increase in sutural density after 6 months of retention, indicating reorganization of the midpalatal suture [14].…”
Section: Introductionmentioning
confidence: 99%
“…Changes are observed in the biologic behavior, morphology, and an increase in the density with aging and skeletal maturation (20). In the past, maxillary occlusal radiographs were used for the evaluation of inter-maxillary suture; on such radiographs, it is difficult to carry out an antero-posterior evaluation of the suture because the image is a 2D representation of a 3D structure, and, due to the superimposition of the nasal structures and the vomer bone on the midpalatal area, misinterpretation of the radiography and discrepancy with morphologic findings are possible (14, 21). CT and CBCT techniques are alternative techniques that can provide 3D and high-resolution images of craniofacial structures (5, 16, 20).…”
Section: Introductionmentioning
confidence: 99%